Geographical distribution of marine and continental climate indices in Libya (Journal of Libya for geographical studies, 2023)
This study deals with the distribution of continental and marine indicators of "Johansson" and "Kerner" in Libya, and these indicators are useful tools for determining comprehensive climate classification for any region in the world. The climatic indicators in Libya were calculated using the mean annual range of temperatures, and average temperatures in April and October, for 22 stations from different locations in Libya, including coastal stations such as Zwara and Derna, and desert stations such as Kufra and Ghadames. And mountainous stations such as Gharyan in West Mountain and Shahat in Green Mountain. The most monitoring periods ranged between 1981-2010. The results showed that marine climate prevails on the Mediterranean coast and the mountainous regions, and there is a slight difference between the values of the two indicators, especially in the transitional areas between the coast and the desert. The relationship between the values of the two indicators showed a negative correlation. Regarding applied; this research may be useful in water, agriculture, and energy research in Libya.
Keywords: Indicators; climatic classifications; marine climate; continental climate; Johansson; Kerner; Libya